2013
DOI: 10.1038/srep01509
|View full text |Cite
|
Sign up to set email alerts
|

A carbon nanotube-infused polysulfone membrane with polyvinyl alcohol layer for treating oil-containing waste water

Abstract: A carbon nanotube (CNT) integrated polymer composite membrane with a polyvinyl alcohol barrier layer has been prepared to separate oil from water for treatment of oil-containing waste water. The CNTs were synthesised using chemical vapour deposition, and a phase inversion method was employed for the blending of the CNTs in the polymer composite solution for casting of the membrane. Relative to the baseline polymer, an increase of 119% in the tensile strength, 77% in the Young's modulus and 258% in the toughnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 40 publications
9
74
1
Order By: Relevance
“…In a recent study reported by Maphutha et al [9], synthesis of MMM containing polysulfone as the substrate and CNTs as the fillers for the treatment of oil-containing water was studied. To further enhance the fouling resistance, the selectivity, and the mechanical strength of the membranes, the top layer of the MMM was covered with a thin layer of polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study reported by Maphutha et al [9], synthesis of MMM containing polysulfone as the substrate and CNTs as the fillers for the treatment of oil-containing water was studied. To further enhance the fouling resistance, the selectivity, and the mechanical strength of the membranes, the top layer of the MMM was covered with a thin layer of polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles, nano-powders, and nanomembranes have been found to have extensive applications in the water sector (Theron et al, 2008;Li et al, 2008;Pendergast and Hoek, 2011;Qu et al, 2013;Maphutha et al, 2013); as a result, interest in these materials for water treatment has increased significantly over the past decade (Roco 2011;De Volder et al, 2013;Humplik et al, 2011). The ability of these nano-materials to remove pathogens in water, adsorb priority water pollutants and degrade chlorination by-products makes them highly desirable for water treatment (Tiwari et al, 2008).…”
Section: Emerging Remediation Trends For the Future Nanotechnologymentioning
confidence: 99%
“…Oil concentrations in wastewater generated in such industries may go up to 1000 mg/L or above (Chakrabarty, Ghoshal, & Purkait, 2008); however, the acceptable discharge limit is only 10-15 mg/L (Maphutha, Moothi, Meyyappan, & Iyuke, 2013). Using ceramic MF membrane, Hua et al (2007) studied the effects of transmembrane pressure (TMP), CFV, oil concentration in feed, pH and salt concentration on the permeate flux, and total organic carbon (TOC) removal efficiency during the separation of oily wastewater.…”
Section: Membrane Filtration Technologiesmentioning
confidence: 99%
“…The results also indicated that the permeate flux decreased either under high salt concentration or under low pH value in the feed solution. Maphutha et al (2013) used a carbon nanotube integrated polymer composite membrane with a polyvinyl alcohol barrier layer to treat oil-containing wastewater. The permeate through the membrane contained oil concentrations below the acceptable 10 mg/L limit with an excellent throughput and oil rejection of over 95%.…”
Section: Membrane Filtration Technologiesmentioning
confidence: 99%